Assessment of body composition in referees and assistant referees professional football - Zoraghi, M. R.; Khoshnam, E.; Solhjo, M. H. (European Journal of Experimental Biology, 2014)
Review to assess body composition, physical fitness, health and design framing programs for athletes is essential. The aim of the present study was to assess body mass index, fat mass, percent body fat, lean body mass and body weight were referees and assistant referees professional football. Subjects of the study were 72 men (age 30-40) who participated is the study voluntarily and were assigned in referees (n=12) and assistant referees (n=12) groups. The subjects of this study were at least 10 years of history in competitions football. Data was analyzed using independent t-test statistical methods. Research findings showed that significant difference between the amount of lean body mass (p=0.013) and body weight (p=0.006) was observed in both groups but no significant difference between BMI levels (p=0.257), fat mass (p=0.152) and fat percentage (p=0.485) referees and assistant referees were observed. Given that the action playing soccer with a referees must be present at the place and at the right time and see the game up close, interpretation of laws, and critical decisions have the for the check the status of useful information rehearses body composition assessment fitness referees and assistant referees provides.